2011
DOI: 10.1109/tmi.2010.2089694
|View full text |Cite
|
Sign up to set email alerts
|

Penalized Maximum Likelihood Reconstruction for Improved Microcalcification Detection in Breast Tomosynthesis

Abstract: We examined the application of an iterative penalized maximum likelihood (PML) reconstruction method for improved detectability of microcalcifications (MCs) in digital breast tomosynthesis (DBT). Localized receiver operating characteristic (LROC) psychophysical studies with human observers and 2D image slices were conducted to evaluate the performance of this reconstruction method and to compare its performance against the commonly used Feldkamp FBP algorithm. DBT projections were generated using rigorous comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 48 publications
0
33
0
1
Order By: Relevance
“…The so-called projection images that are acquired during the tube movement are reconstructed to a 3D volume with mathematical algorithms, similar to computed tomography (CT). Filtered back-projection (FBP) has frequently been used because of its speed, but several research groups are developing and evaluating this and other types of reconstruction algorithms, for example maximum likelihood expectation maximization (MLEM) and simultaneous algebraic reconstruction technique (SART) [39][40][41][42][43]. No general conclusion on which algorithm is the better one has yet been reached.…”
Section: Breast Tomosynthesismentioning
confidence: 99%
“…The so-called projection images that are acquired during the tube movement are reconstructed to a 3D volume with mathematical algorithms, similar to computed tomography (CT). Filtered back-projection (FBP) has frequently been used because of its speed, but several research groups are developing and evaluating this and other types of reconstruction algorithms, for example maximum likelihood expectation maximization (MLEM) and simultaneous algebraic reconstruction technique (SART) [39][40][41][42][43]. No general conclusion on which algorithm is the better one has yet been reached.…”
Section: Breast Tomosynthesismentioning
confidence: 99%
“…Although a number of studies have investigated the performance of iterative reconstruction for CT, 3 very few have been addressed specifically to the upcoming new modality of breast CT. Previously, Das et al 4 observed improvements in the accuracy of detecting microcalcifications, when using statistical iterative reconstruction (SIR) for breast tomosynthesis. In this study, we investigate SIR algorithms for breast CT.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, an algebraic matrix is used to selectively identify and then subtract noise from the image according to a mathematical model. The objective with MLEM (statistical method) is to identify the reconstructed image that maximizes the likelihood of having observed the particular projection measurements [15]. In the MLEM algorithm, because high-frequency noise in the data is amplified by each iteration of the reconstruction algorithm, a smaller number of iterations may be optimal for detection of low-contrast objects, such as small tumors [3].…”
Section: Discussionmentioning
confidence: 99%